Automated electric generators test bench for low power wind energy applications - Juan Carlos Agotegaray; Andrea Pinzón; Emanuel Lera (Revista Elektrón, 2020)
This paper presents the development of an automated electric generators test bench for low power wind energy in urban applications. The bench allows testing electric generator under similar operating conditions to real, electric generator coupled to a wind turbine in urban environments, which allows to determine specific parameters: electric current, voltage, power.